Benefits and Challenges in Using Seroprevalence Data to Inform Models for Measles and Rubella Elimination. (19th March 2018) - Winter, Amy K; Martinez, Micaela E; Cutts, Felicity T; Moss, William J; Ferrari, Matt J; McKee, Amalie; Lessler, Justin; Hayford, Kyla; Wallinga, Jacco; Metcalf, C Jess E
Abstract : We use simulations to highlight how (accounting for the dynamical context) high-quality measles and rubella serological surveys can be used to inform key control and elimination questions if the challenges of conducting, analyzing, and interpreting them are overcome. Abstract: Background: Control efforts for measles and rubella are intensifying globally. It becomes increasingly important to identify and reach remaining susceptible populations as elimination is approached. Methods: Serological surveys for measles and rubella can potentially measure susceptibility directly, but their use remains rare. In this study, using simulations, we outline key subtleties in interpretation associated with the dynamic context of age-specific immunity, highlighting how the patterns of immunity predicted from disease surveillance and vaccination coverage data may be misleading. Results: High-quality representative serosurveys could provide a more accurate assessment of immunity if challenges of conducting, analyzing, and interpreting them are overcome. We frame the core disease control and elimination questions that could be addressed by improved serological tools, discussing challenges and suggesting approaches to increase the feasibility and sustainability of the tool. Conclusions: Accounting for the dynamical context, serosurveys could play a key role in efforts to achieve and sustain elimination.